Adapting to change : the business of climate resilience - Goodman, Ann. (Giving voice to values on business ethics and corporate social responsibility collection., 2016)
This book examines emerging business reactions to, plans, and preparations for climate events (e.g., fires, storms, floods, and hurricanes) and trends (e.g., droughts) from leading companies in strategic sectors: technology, telecommunications, food, banking, and insurance.